Implementasi Kecerdasan Buatan Dalam Optimalisasi Proses Produksi Pada Industri Manufaktur - Saputra, Hasar; Arifin, Muhammad (Computer Science and Information Technology, 2024)
Increasingly tight global competition requires industries to continue to innovate and improve production efficiency. Artificial Intelligence (AI) has emerged as an innovative technology that can optimize various aspects of the production process. The purpose of this study is to analyze the impact of implementing Artificial Intelligence on optimizing the production process. Through a literature review and case analysis, this study identifies various applications of Artificial Intelligence such as maintenance forecasting, quality control, and production planning. The results of the study indicate that Artificial Intelligence has great potential to increase productivity, reduce production costs, and improve product quality. However, the study also revealed several challenges in implementing Artificial Intelligence.